EFFECTIVENESS OF USE OF BENSON RELAXATION THERAPY, DZIKIR AND MUSIC DANGDUT ON PAIN SCALE LEVELS IN POST-OPERATIVE PATIENTS APPENDICTOMY AT BHAYANGKARA BRIMOB HOSPITAL - Sariningrum, Indah Ika; Mochartini, Tri (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2025)
Background: WHO in 2021 stated that the incidence of appendicitis in the world reached 7% of the total world population. Asia 2.6%, United States 7% of the total population. In Southeast Asia, Indonesia ranks first with a prevalence of 0.05%, followed by the Philippines at 0.022% and Vietnam at 0.02%. One of the medical treatments for appendicitis patients is surgery. The problem that arises after surgery is pain. Post-surgical pain management to reduce post-surgical pain is carried out using pharmacological and non-pharmacological approaches. Non-pharmacological management is by giving hot and cold compresses, massage, listening distraction, breathing relaxation techniques in dhikr and music therapy techniques. Objective: To determine the effectiveness of using Benson relaxation therapy, dhikr, and dangdut music on pain scale levels in post-appendectomy patients. Methods: Quasi experimental with a three group pretest-posttest design. The sample in this study was all post-appendectomy patients at the hospital. Bhayangkara Brimob in November 2023 as many as 30 people. The sampling technique uses total sampling. Results: The majority of respondents before being given the intervention experienced moderate pain and after the intervention the majority of respondents experienced mild pain. Benson relaxation therapy was more effective in reducing the pain scale in pre-appendectomy patients compared to dhikr therapy and dangdut music (p=0.047). Conclusions and Suggestions: Benson relaxation therapy is more effective in reducing the pain scale in pre-appendectomy patients compared to dhikr therapy and dangdut music. It is hoped that Benson relaxation therapy can be used as a non-pharmacological therapy option to reduce the pain scale in post-operative patients.